THE PERSPECTIVE OF THE THEORY OF PLANNED BEHAVIOR AND FINANCIAL LITERACY ON THE INTENSITY OF E-WALLET USAGE (STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, STATE UNIVERSITY OF GORONTALO, CLASS OF 2024) - Pontoh, Siti Nurhaliza; Hafid, Radia; Dama, Maya Novrita; Panigoro, Meyko; Damiti, Fatmawati (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to determine and analyze the influence of the Theory of Planned Behavior and Financial Literacy on the Intensity of E-Wallet Usage among university students. This research employs a quantitative method. Data were collected through the distribution of questionnaires to 88 students of the Faculty of Economics and Business at Gorontalo State University and analyzed using SPSS version 25 by conducting validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, and F-test. The results show that: (1) the Theory of Planned Behavior has a positive and significant effect on the Intensity of E-Wallet Usage, (2) Financial Literacy has a positive and significant effect on the Intensity of E-Wallet Usage, and (3) both variables simultaneously exert a significant influence. These findings indicate that behavior in using e-wallets is influenced by psychological elements and financial literacy skills Both factors play a crucial role in shaping smart, effective, and responsible digital financial behavior in today's era.